2015
DOI: 10.1249/mss.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Immersion during Exercise on Cerebral Blood Flow

Abstract: Our findings suggest that water-based exercise augments cerebral blood flow, relative to land-based exercise of similar intensity, in healthy humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 35 publications
4
64
1
Order By: Relevance
“…Due to the aquatic and dynamic environment utilized, we were unable to measure MAP on a beat‐by‐beat basis or during exercise. However, it has been previously shown that MAP has a greater increase during water‐immersed upright exercise compared to that which occurs on land (Pugh et al, ). Furthermore, we only report data from one swimming style (i.e., breast‐stroke).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to the aquatic and dynamic environment utilized, we were unable to measure MAP on a beat‐by‐beat basis or during exercise. However, it has been previously shown that MAP has a greater increase during water‐immersed upright exercise compared to that which occurs on land (Pugh et al, ). Furthermore, we only report data from one swimming style (i.e., breast‐stroke).…”
Section: Discussionmentioning
confidence: 94%
“…Uniquely, the current study delineated the factors behind changes in MCAv mean during breast‐stroke swimming. Previous studies have illustrated that upright aquatic exercise (i.e., walking/running and box stepping) increases MCAv mean across a range of intensities (Pugh et al, ; Parfitt et al, ), which has been contributed, in part, to changes in PETCO 2 (Pugh et al, ). Furthermore, we illustrated that swimming shows a similar MCAv mean response as for other dynamic large muscle‐group exercise (unpublished data from our lab).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently this concept has been illustrated via water immersion, where CBF increases in a similar magnitude to that obtained during landbased exercise, 128 and more so when water immersion was combined with exercise. 129 How this then translates to longerterm effects (i.e., after a training intervention) has not yet been reported, but the combined strategy may result in greater improvements in cerebrovascular function than previously reported from a standard land-and aerobic-based training study. 130 Such a training strategy may be a powerful adjunct to increase the shear-stress stimulus for clinical populations with impaired mobility as a consequence of injury (e.g., hip fracture) or large body mass (e.g., obese).…”
Section: Optimizing Cerebrovascular Adaptation Through Brain-targetedmentioning
confidence: 96%
“…Exercising in water has recently been promoted as a method by which to enhance shear-stress-mediated vascular adaptation in the brain (Pugh et al 2014). Pugh and colleagues demonstrated greater increases in CBF velocity (by ß10%) during water-based activity compared with matched-intensity land-based activity.…”
Section: Exploring Novel Targeted Approachesmentioning
confidence: 99%